1985
DOI: 10.1111/j.1476-5381.1985.tb09461.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of 5‐hydroxytryptamine‐induced head‐twitch response by drugs acting at GABA and related receptors

Abstract: The effects of drugs acting at the γ‐aminobutyric acid (GABA) receptors and other chloride ionophore‐related sites have been studied for their ability to modulate the head‐twitch induced by 1–5‐hydroxytryptophan (5‐HTP) in the mouse. The GABAa receptor agonists, muscimol, imidazoleacetic acid and 3‐aminopropanesulphonic acid, produced a dose‐related potentiation, while bicuculline inhibited the head‐twitch. The GABAb receptor agonist, baclofen, produced dose‐related inhibition. Diazepam potentiated the head‐tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…However, this speculation is also unlikely because there was no difference in the effect of DOI on the secretion of corticosterone between non-diabetic and diabetic mice. It has been reported that noradrenergic and GABA/benzodiazepine systems modulate the HTRs induced by 5-HT receptor agonists (Handley and Brown 1982;Handley and Singh 1985). We previously reported that diabetic mice showed the decreased turnover rates of noradrenaline in the frontal cortex (Kamei and Ohsawa 1997) and altered function of benzodiazepine receptors (Kamei and Ohsawa 2000).…”
Section: Discussionmentioning
confidence: 98%
“…However, this speculation is also unlikely because there was no difference in the effect of DOI on the secretion of corticosterone between non-diabetic and diabetic mice. It has been reported that noradrenergic and GABA/benzodiazepine systems modulate the HTRs induced by 5-HT receptor agonists (Handley and Brown 1982;Handley and Singh 1985). We previously reported that diabetic mice showed the decreased turnover rates of noradrenaline in the frontal cortex (Kamei and Ohsawa 1997) and altered function of benzodiazepine receptors (Kamei and Ohsawa 2000).…”
Section: Discussionmentioning
confidence: 98%
“…For example, the disruption of GABAergic inhibition by a reverse GABA A receptor agonist (FG-7142) elicited c-fos expression changes in the orexin neuron hypothalamic network involved in stress and panic [82]. An important role for the GABAergic system has also been reported in the context of hallucinations [83]. Altogether, these mechanisms may possibly lead to the development of a multiindication drug discovery assay.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have shown previously that PKCγ regulates ethanol-stimulated GABA A receptor function in cortex (Harris et al, 1995). It has been shown that GABAergic drugs modulate head twitch behavior in rodents, perhaps through interaction with 5-HT 2 receptors (Handley and Singh, 1985;Moser and Redfern, 1988;Tadano et al, 2001). Feng et al (2001) reported that activation of 5-HT 2 receptors in the prefrontal cortex of rats increased in vitro PKC activity toward GABA A receptor γ 2 subunits.…”
Section: Behavioral Assessments Of 5ht 2a/c Receptorsmentioning
confidence: 99%